Impact of attendance management on improving employee’s performance: Focusing on Acorn Infrastructure Service Ltd. - Fariha, Nabila (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.